Rebecca Black: capstone - Black, Rebecca, artist (Colorado State University. Libraries, 2013)
The artist's statement: I am inspired by the light found in water and distorted reflections. I enjoy both the invention and emotive quality of underwater imagery. Water conveys multiple emotions, and often seems otherworldly. Water has it's own set of rules and conditions, such as weightlessness and disorientation, which allow me to explore ambiguity in my paintings. When my paintings are ambiguous, the viewer is forced to investigate the entire painting and form their own meaning to the piece. As light moves through water it forms varying shapes on the figure and the surface. These organic shapes interest me because of their line quality and the stylization they can bring to the image. Furthermore, water has vibrant and natural color that I adapt and exaggerate to set the mood within my paintings. I gather several sources of inspiration, compiling images from other artists, my own photos and life experiences. Using multiple images frees me from remaining entirely true to my sources. I paint from a source for an hour or two, then continue working for a while without the image, changing the form and placement of the subject to better convey meaning. Painting figures in my compositions allows the viewer and the artist to establish an immediate connection with the piece. The subject in the painting places the viewer either within or outside of the water.
Colorado State University Art Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.